Notes on Afrotropical Cydnidae (Heteroptera) with emphasis on vehicle-mounted net samples and description of a new species from Liberia, West Africa - Krüger, Andreas; Lis, Jerzy A. (Zootaxa, 2019)
Notes on the Cydnidae fauna in Liberia, sampled with a vehicle-mounted net, the species taxonomy and general distribution are reported, including the description of Chilocoris elongatus sp. nov. In addition, new country records are provided for Angola, Ethiopia, Gabon, Guine    a-Bissau, Namibia, Niger, Republic of South Africa, Sierra Leone, Tanzania, Togo, Uganda, and Zimbabwe.